Power management ICs for portable device - Li, Xin (2015)
Prolonging the running time of Portable devices motivate us continuously to improve the efficiency and power consumption of power management integrated circuits (ICs) in portable devices due to the little progress in the scaling of battery voltage. In order to extend the working life, the energy harvesting technology is equipped in the device as a backup source or the main source for the portable device and wireless sensor, hence, the design challenge is that power management ICs can operate with extreme low power and low voltage. Therefore, an ultra-low voltage reference circuit with ultra-low power consumption of 180nW is proposed in this research work. Portable device usually switches alternatingly between high load and low load. However, the control method is optimized to make the DC-DC converter so that it operates in high conversion efficiency particularly only in one load or another. As a result, Hybrid control method is proposed to maintain the high conversion efficiency of converter for a wide load range. Due to the fact that mobile portable device operate most of their time in low load condition, a novel Dead time and Reverse inductor current controller are developed to improve the efficiency of DC-DC converter dedicated for low load conditions. Overall, the design objective focus on the improvement of efficiency for power management ICs so as to meet the requirement imposed by the source and load.